Anadolu Türk âsâr ve mahkûkâtı tetebbuâtına esâs - Eldem, Mübârek Galip, 1871-1938. ([Ankara] [Ankara])
2 cilt (1. c. 54 sayfa, [41] yaprak resim, çizim, plan ; 2. c. 66 sayfa, [12] resim, çizim, plan)